Cover Crops and Ecosystem Services: Insights from Studies in Temperate Soils. (1st November 2015) - Blanco‐Canqui, Humberto; Shaver, Tim M.; Lindquist, John L.; Shapiro, Charles A.; Elmore, Roger W.; Francis, Charles A.; Hergert, Gary W.
Abstract : Cover crops (CCs) can provide multiple soil, agricultural production, and environmental benefits. However, a better understanding of such potential ecosystem services is needed. We summarized the current state of knowledge of CC effects on soil C stocks, soil erosion, physical properties, soil water, nutrients, microbial properties, weed control, crop yields, expanded uses, and economics and highlighted research needs. Our review indicates that CCs are multifunctional. Cover crops increase soil organic C stocks (0.1–1 Mg ha −1 yr −1 ) with the magnitude depending on biomass amount, years in CCs, and initial soil C level. Runoff loss can decrease by up to 80% and sediment loss from 40 to 96% with CCs. Wind erosion potential also decreases with CCs, but studies are few. Cover crops alleviate soil compaction, improve soil structural and hydraulic properties, moderate soil temperature, improve microbial properties, recycle nutrients, and suppress weeds. Cover crops increase or have no effect on crop yields but reduce yields in water‐limited regions by reducing available water for the subsequent crops. The few available studies indicate that grazing and haying of CCs do not adversely affect soil and crop production, which suggests that CC biomass removal for livestock or biofuel production can be another benefit from CCs. Overall, CCs provide numerous ecosystem services (i.e., soil, crop–livestock systems, and environment), although the magnitude of benefits is highly site specific. More research data are needed on the (i) multi‐functionality of CCs for different climates and management scenarios and (ii) short‐ and long‐term economic return from CCs.